Mountain meteorology : fundamentals and applications - Whiteman, C. David, 1946- (Oxford University Press, 2000)
Preface. About the author. Acknowledgments. Part 1. Mountain Climates. 1. Four Factors that Determine Climate. 2. Mountain Climates of North America. Part 2. An Introduction to the Atmosphere. 3. Atmospheric Scales of Motion and Atmospheric Composition. 4. Atmospheric Structure and the Earth's Boundary Layer. 5. Pressure and Winds. 6. Air masses and Fronts. 7. Clouds and Fogs. 8. Precipitation. 9. Weather Maps, Forecasts and Data. Part 3. Mountain Winds. 10. Terrain-Forced Flows. 11. Diurnal Mountain Winds. Part 4. Selected Applications of Mountain Meteorology. 12. Air Pollution Dispersion. 13.